Wetting characteristics and regularity of AISI 4135 steel in marine splash zone - Huang, Y.; Yu, X.; Zheng, M.; Qu, W.; Yadav, A.; De Marco, Roland (2015)
The corrosion rate of steels in marine splash zone is high, and it is generally considered to be due to the environmental characteristics of this zone. One of the important distinctions between the marine splash zone and the normal atmospheric zone is the wetting condition of steel surfaces. However even in the same splash zone, the corrosion rate of one spot is different to that of the other ones on the surface of one steel pile, thereby on which a corrosion rate peak should exist at a specific spot. In order to reveal the nature of the difference in corrosion rate at different positions of a steel pile, the variations of the wetting condition of steel specimens with tidal movement was monitored, while the specimens located at different positions along a vertical line passing the tide zone. It follows that the wetting degree of the steel specimen in the splash zone is closely related with its location and the tidal movement, and which substantially follows an overall trend that the wetting degree increases with the rising tide level and decrease with the lowering tide level; the wetting degree of the steel specimen increases with the increase of exposure time. But for a specific moment, a certain relationship dose not exist for the wetting degree with the tide movement and the location of steel specimen. Even though by the time of the low tide level the steel specimen located in splash zone is still in a wet condition due to the effect of the high air humidity and flying seawater foam, which correlates also to the high moisture absorption characteristics of corrosion products scale on the carbon steel. The extreme corrosion rate of the steel in splash zone corresponds to a specific wetting degree. Furthermore, on the area below the extreme point, thin water film on the surface of steel specimens can often be observed by naked eyes, which is consistent with the relationship between corrosion rate and thickness of liquid film on the metal surface.